Impact of Jet-Grouting Pressure on the Strength and Deformation Characteristics of Sandy and Clayey Soils in the Compression Zone - Akin, Mutluhan; Akkaya, Ismail; Akin, Muge K.; Ozvan, Ali; Ak, Yusuf (Korean Society of Civil Engineers-ksce, 2019)
Jet-grouting as a soil improvement method is extensively preferred in today's civil engineering practice. High-modulus grout columns constructed by extremely high jetting pressures displace the surrounding soil causing a densification in soil particles. Accordingly, the strength as well as the deformation characteristics of subsurface soils are relatively improved across the compression zone which is under the influence of high jetting pressure. In this study, the modification of soil properties in compression zone after jet-grouting in sandy and clayey soils is investigated by standard penetration tests (SPT) and multi-channel analysis of surface waves (MASW) performed at a couple of construction sites along established jet-grout column rows. The in-situ test results point out significant improvement of the measured parameters compared to initial values. The rate of enhancement in the compression zone is higher in sandy strata than that of clayey deposits. The strengthening of soil due to jetting pressure is validated by finite element analyses as well. Furthermore, very low shear strain values are obtained in clayey soils with respect to the improved characteristics of compression zone representing extremely low shear deformation under foundation.
Akin, Mutluhan/0000-0002-5752-6949;
Keywords: Jet-Grouting; Soil Improvement; Soil-Cement Mixture Column; Compression Zone; SPT; S-Wave Velocity